Characterization and modeling cure- and pressure-dependent thermo-mechanical and shrinkage behavior of fast curing epoxy resins. (April 2022) - Lorenz, N.; Müller-Pabel, M.; Gerritzen, J.; Müller, J.; Gröger, B.; Schneider, D.; Fischer, K.; Gude, M.; Hopmann, Ch.
Abstract: A fast crosslinking reaction is crucial for the economical production of automotive components in liquid composite molding (LCM) processes. Although a large number of works have focused on modeling of shrinkage induced surface waviness and part distortions and the underlying phenomena an accurate determination of material properties under consideration of processing parameters still represents a major challenge for fast-curing epoxy resins. Fast-curing epoxy polymers allow manufacturing of thermoset composite parts in minutes while entailing a highly exothermic heat generation. Cure is carried out under elevated temperatures and pressures and is accompanied by a change in density due to chemical shrinkage and followed by thermal contraction. In the present study, comprehensive results on the characterization of thermo-mechanical properties, pressure dependent reaction kinetics and shrinkage are presented for a fast curing epoxy resin. The obtained results give important advice for improved process modeling and facilitate prioritisation for future characterisation of fast-curing epoxy resins. Highlights: Pressure dependence of curing reaction kinetics. In-process determination of pressure dependent chemical shrinkage. Coupled modeling of pressure and cure dependent chemical shrinkage. Material model input for improved process simulation of LCM.